An iterative frequency-domain decision-feedback receiver for MC-CDMA schemes - Dinis, Rui (2013)
The MC-CDMA techniques (multicarrier code division multiple access) combine a CDMA scheme with OFDM modulation (orthogonal frequency division multiplexing), so as to allow high transmission rates over severely time-dispersive channels without the need of a complex receiver implementation. We propose an iterative frequency-domain decision-feedback receiver for MC-CDMA signals. The proposed receiver has excellent performance, close to the single-code MFB (matched filter bound), even for severe time-dispersive scenarios and/or in the presence of strong interfering channels.